Propriedades mecânicas e reológicas de compósitos de copolímero de etileno acetato modificado com seus rejeitos advindos da indústria calçadista - Paiva Júnior, Cristiano Zenaide (2020)
Nowadays, there is great interest in the reduction and use of waste generated by the industry. In addition to the environmental gain, economic gains can be obtained with better management of these tailings. There are still not many studies for the use of waste generated by the footwear industry, mainly in the use of EVA waste. In this work, the influence of the incorporation of micronized EVA tailings from the injection process of midsoles for sports shoes in EVA composites was evaluated. The defects of injection branches and defective midsoles were crushed and micronized. Three mixtures were prepared with 15 phr, 25 phr and 35phr of micronized waste. The mechanical, thermal and rheological properties were evaluated in comparison to the compound currently used in the industry. The micronization of the EVA tailings reached a micrometric particle size with an average diameter of 53.06 μm. In thermogravimetry (TG / DTG) it was observed that with the increase in the micronized EVA content, there was a delay in the deacetylation of EVA composites when compared to the normal production EVA compound. A statistical study with linear regression analysis of the mechanical properties was conducted to investigate the compositions that gave rise to the best properties. The results indicated that shrinkage and tear strength properties increased with EVA-w content due to EVA-w acts as nucleation cell agent increasing cell density of EVA foam. The compression set property increased with EVA-w content due to decrease of matrix elasticity. For hardness, tensile strength and elongation at break was observed that EVA-w acts as reinforcement filler. A statistical study based on performance indices of mechanical properties, as well a cost analysis, both were carried out to investigate the composites. For the mechanical properties, except the average linear shrinkage obtained for the composite with 35 phr of EVA-w, all other studied composites met the specifications for midsole of sports shoes. The composites submitted to the torque rheometer were analyzed by Fourier transform infrared spectroscopy (FTIR) which showed that during the mixing there were no new cross-links and that with the addition of the micronized tailing, the calcium carbonate band tends not to appear. In addition, the influence of the addition of micronized EVA on the rheological parameters of EVA compounds was also evaluated by torque rheometry. It was found that with the increase of the micronized waste there was an increase in the shear stress and that for all samples a pseudoplastic behavior was observed. A cost analysis of the studied composites was performed and it was observed that with the increase of the incorporation of the tailings there is a decrease in the cost / kg of the formulations.